An Analysis of English Jargon Used in MasterChef Indonesia Season 8 - Bayu Seto Wibowo; Sri Wulandari; Kristanti Yuntoro Putri (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2022)
This research aimed to know the jargon used in MasterChef Indonesia Season 8 which is broadcasted on tv namely RCTI. In this research, the researcher applied the descriptive qualitative method. The source of the data is the utterances in the conversation between the participants and the judges of MasterChef season 8 . The data of this research is taken from the utterances of the judges and the participants of Masterchef Indonesia season 8 which contains jargon. While the data source of this research is taken from the videos of Masterchef Indonesia on the Vision+ Website namely Visionplus.id. Vision+ is a digital live TV and Video On Demand (VOD) streaming media service owned by MNC Group. The researcher employed a free-of-conversation listening technique and the note-taking technique. This technique is carried out by observing the utterances used in the conversation between the three judges namely, Chef Arnold, Chef Juna, and Chef Renata, and the three participants namely, Adi, Jesselyn, and Nadya of MasterChef Indonesia Season 8 which contains Jargon. The result of this research found 25 jargon used in the conversation between judges and the participants of MasterChef Indonesia season 8. Of the 25 data, 18 jargon was in the form of words and 7 jargon in the form of phrases. This research found some functions of Jargon that were giving a person a sense of belonging to a specific group, making it easier for a person to communicate with their group, and as an effective signal for identification.